The development of an iPad application for the pain assessment of individuals with developmental disabilities and complex communication needs. Issue 4 (4th July 2021) - Guard, Alyssa; Konz, Michelle; Smith, Roger O.; Engel, Joyce M.; Keating, Thomas
ABSTRACT: Aims : Develop a new pain assessment for youth with communication challenges. The Guard-Putzer Pain Assessment Domains (gPAD) mobile application (app) was designed and tested as a universally accessible way for youth, ages 7–12 years, with a developmental disability (DD) to express their pain experiences through self-report. Methods : A two-phase process developed the design for an app, created an interactive prototype, and tested its face validity and user interface. This work included a comprehensive scoping review of current assessments and pain apps as well as a survey to obtain descriptive data on the clinical practicality of the gPAD to guide the app design. Additionally, 15 therapists reviewed the gPAD assessment. Results : Thirteen respondents (87%) agreed to the statement that they would use the gPAD for this population. School-based practitioners seemed to highlight the most significant needs for the app. Conclusions : Advancement of this app could mainstream the assessment of pain in youth with DD, and other potential populations.